2021
DOI: 10.21608/jcbr.2021.63456.1178
|View full text |Cite
|
Sign up to set email alerts
|

Impact of SOX2 and CD44 as Cancer Stem Cell Markers in Urinary Bladder Carcinoma: Thesis Abstract

Abstract: Background: In Egypt, bladder cancer (BC) is the third common malignant tumor. The most important items of CSCs regulatory core are transcription factors like SOX2. The cell adhesion molecule CD44 has also been found as a cell surface marker with CSCs in multiple types of tumors, like BC. Aim: This study was conducted to detect the expression of SOX2 and CD44 and correlate their expression with the available pathological parameters. Materials and Methods: The study was done on 80 cases of BC (60 cases of trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 31 publications
4
2
0
Order By: Relevance
“…In the current study, we found a significant association between SOX2 expression and stage P =0.01 which was in line with the results of previous IHC studies as those made by Fekry et al, 37 Bao et al, 36 and Amer and Amer 35 …”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In the current study, we found a significant association between SOX2 expression and stage P =0.01 which was in line with the results of previous IHC studies as those made by Fekry et al, 37 Bao et al, 36 and Amer and Amer 35 …”
Section: Discussionsupporting
confidence: 93%
“…We found a significant association between SOX2 expression and high grade (P ≤ 0.001), this is in agreement with the study made by Bao et al, 36 Fekry et al, 37 and Gayyed et al 38 who found a significant association between SOX2 expression and grade, but in contrary to what reported by Amer and Amer 35 who failed to find significant correlation between SOX2 expression and tumor grade (P = 0.267), also in the study made by Bayoumi et al, 39 who did not find any significant relation between SOX2 expression and tumor grade.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations